Socio-Economic Impacts of Landslides and Applied Mitigation Techniques: A Case Study in Bagnaskali, Nepal - Shakya, Anushka; Sigdel, Pawan; Pokhrel, Saroj (Journal of Sustainability and Environmental Management, 2023)
This study aimed to estimate the socio-economic impacts of landslides and identify mitigation techniques being applied for landslide control in Bagnaskali rural municipality, Palpa. Purposive sampling was conducted to focus the research on plots with frequent landslide occurrences. Out of the 20 identified landslide-prone sites, a random sampling method was used to ensure representative data collection with a 40% sampling intensity. Data were collected through direct observation, transect walks, and household surveys conducted in areas prone to landslides. Additionally, discussions were held with key informants, the technical team, and experts in the field to validate the collected data. In Bagnaskali rural municipality in the year 2020, six households reported damage, two cases of death occurred, 24 livestock fatalities were recorded, and there was damage to cultural heritage due to landslides, resulting in social losses. Affected communities also incurred compensatory losses ranging from NRs 10 to 50 lakhs due to the destruction of water resources, road blockages, and agricultural land damage. As mitigation measures for landslides, the municipality applied civil engineering techniques such as gabion walls, masonry, culverts, check dams, and reinforced concrete (RCC), as well as bioengineering techniques including plantation, wattling, and brush-layering. Civil engineering techniques were prioritized for mitigating landslides, with bioengineering serving as a supporting base. Plots where both civil and bioengineering techniques were employed together exhibited greater slope stability and reduced vulnerability. Therefore, it is recommended to use mitigation techniques that stabilize slopes and reinforce the soil to control landslide hazards effectively. To successfully reduce landslides and protect vulnerable communities, comprehensive policies, laws, and investments are required. Technical and financial assistance from governmental and non-governmental sectors is essential to minimize the impacts of landslides and implement the most effective mitigation techniques for landslide control.